Industry 4.0, circular economy and sustainability in the food industry: A literature review - Aguado Rodriguez, Renato Jose (2023)
The purpose of this study is to find out which Industry 4.0 tools are applicable in the food supply chain to implement sustainability practices positively in the food supply chain; since food supply chains have the characteristic of being among the most inefficient in terms of sustainability and the biggest generators of waste and resource consumption. Since the applications of Industry 4.0 technologies for development seem to attract more and more attention from professionals and academics, and in turn these have had a positive impact on sustainability in other types of industries, we seek to know which Industry 4.0 tools have a greater impact on the sustainability of food supply chains. In this context, an analytical approach is proposed to broadly understand the sustainable performance of I4.0 in the food sector. Through a systematic review, the article aims to obtain definitions of the concepts involved and their relationships and implementations in order to know the tools capable of generating sustainability in the food supply chain and to be able to answer the following research questions: ¿ What are the Industry 4.0 tools that positively influence sustainability aspects in FSCs? ¿Which tools are better than others for optimizing sustainability in FSC? In order to be able to answer these research questions,the articles obtained in the search were analyzed using trend and bibliometric analysis. In addition, the study is in charge of defining and relating the concepts of industry 4.0, circular economy and sustainability in the food supply chain.